EFIKASI CAMPURAN MINYAK CENGKEH DAN EKSTRAK BIJI MIMBA UNTUK PENGENDALIAN PENYAKIT KARAT (PHAKOPSORA PACHYRHIZI) PADA KEDELAI (GLYCINE MAX) - ., Sumartini (Universitas Lampung, 2016)
Efficacy of clove oil and neem extract control rust (Phakopsora rapachyrhizi) disease on soybean (Glycine max). Rust is the major disease on soybean. It was widely spread in almost all soybean production areas in the world. Yield losses can reach 85%. One of the control measured was sprayed with a mixture of clove oil and neem extract. The objective of the research was found the information of the clove oil and neem extract effectivity control soybean rust. The research consisted of two phases as followed: 1) the efficacy of clove oil and neem extract dilution control soybean rust disease. 2) the efficacy of clove oil, neem extract and soap berry (Sapindus rarak) extract control soybean rust disease. The research was conducted at Kendalpayak Experimental Station and the green house of Indonesian Legumes and Tuber Crops Research Institute, Malang District, in dry season of 2012 and 2013 respectively. The research was arranged in randomized block design. Treatments were various comparison between clove oil, neem extract and soap berry. Parameters observed were rust disease intensity and yield components. Results showed that a mixture of clove oil and neem extract with ratio of 60:40 (v:v) can inhibit rust disease intensity by 45% compared with control, increase the number of pods by 60% and preventing the yieldloss of 20%. Furthermore, a mixture of clove oil, neem extract and berry soap (Sapindus rarak) with a 50:30:20 ratio (v:v:v) can inhibit rust disease intensity up to 28% and 24% in the field and green house respectively and prevent yield loss by 12%.